Chapter 9 Informing Practice Through Collaboration: Listening to Colonising Histories and Aboriginal Music - Foster, Shannon (Taylor & Francis, 2021)
This chapter describes an interdisciplinary and intercultural method for writing about historical performances of music and dance by Aboriginal people, and to inform collaborative performances with Aboriginal musicians. It discusses an approach of listening to history through current Indigenous knowledges, and interrogates how seeking to understand the continuities and disruptions of culture through the experiences of living Aboriginal people allows for new interpretations of archival sources. In combining Indigenous knowledges with historical methods, the chapter responds to Aileen Moreton Robinson's (2000) critique of scholarly approaches that contrast the 'traditional' and 'contemporary' Aboriginal subject, while erasing ongoing colonising influences. The chapter presents a song as methodology and practice, to sing up story and knowledges from history in the present.